Sleep-related metacognitions in inpatients with mental disorders - Anzenberger, Elisabeth; Schredl, Michael; Schilling, Claudia (European archives of psychiatry and clinical neuroscience, 2025)
Background Sleep difficulties are a well-known issue among patients with mental disorders. Sleep related metacognitions often play a role in the etiology of sleep disturbances. This study examined the role of sleep-related metacognitions in a sample of psychiatric inpatients. Methods A total of 75 patients admitted to the psychiatric clinic of the Central Institute of Mental Health (CIMH) in Mannheim, Germany, were included in the study. The participants completed a series of psychometric questionnaires, including the Metacognitive Questionnaire for Insomnia (MCQ-I 20), the Patient Health Questionnaire (PHQ-9) and the Insomnia Severity Index (ISI). Results The psychiatric patient sample exhibited significantly elevated scores on the MCQ-I 20 when compared to a healthy control group and demonstrated comparable scores to a group of insomnia patients. Sleep-related metacognitions in the psychiatric patient sample correlated significantly with increased depression levels and insomnia symptoms. Conclusions The findings of this study provide evidence that sleep-related metacognitions play a role in the etiology of sleep problems in patients with mental disorders.
Gesehen am 09.10.2025